Magnetic Properties of Multisegmented Cylindrical Nanoparticles with Alternating Magnetic Wire and Tube Segments - Escrig-Murua, J; Salazar-Aravena, D; Corona-Gonzalez, R (2013)
Sin Editorial Disponible